1980
DOI: 10.1085/jgp.75.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Calcium effects on frog retinal cyclic guanosine 3', 5'-monophosphate levels and their light-initiated rate of decay.

Abstract: A BSTRAC T When retinal sections were isolated from dark-adapted bullfrogs and placed in normal Ringer's solution, they contained 40.7 :t: 0.2 pmol cGMP/ mg protein (mean :t: SEM, 30 samples). When isolated, dark-adapted retinal sections were removed from normal Ringer's solution and placed in calciumdeficient Ringer's solution with 3 mM EGTA, there was about a threefold rise in cyclic GMP (cGMP) levels by 1.5 min and about a 10-fold rise by 5 rain. The cGMP level remained high with no detectable decrease for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…First, the procedures used to change the internal concentration of Ca2+ and cGMP may affect other cell functions (Bianchi, 1961;Sheppard, 1970;Plagemann, 1974;Gaska, Canter & Shelanski, 1975;Klausner, Bhalla, Dragsten, Hoover & Karnovsky, 1980). A second problem is that cGMP and Ca2+ may play interacting roles in rod physiology since changes in the concentration ofone change the concentration ofthe other (Cohen et al 1978;Kilbride & Ebrey, 1979;Kilbride, 1980;Polans et al 1981). Despite these complications, the present results can be used to help either validate or invalidate some of the currently popular models of photoreceptor excitation.…”
Section: Discussionmentioning
confidence: 93%
“…First, the procedures used to change the internal concentration of Ca2+ and cGMP may affect other cell functions (Bianchi, 1961;Sheppard, 1970;Plagemann, 1974;Gaska, Canter & Shelanski, 1975;Klausner, Bhalla, Dragsten, Hoover & Karnovsky, 1980). A second problem is that cGMP and Ca2+ may play interacting roles in rod physiology since changes in the concentration ofone change the concentration ofthe other (Cohen et al 1978;Kilbride & Ebrey, 1979;Kilbride, 1980;Polans et al 1981). Despite these complications, the present results can be used to help either validate or invalidate some of the currently popular models of photoreceptor excitation.…”
Section: Discussionmentioning
confidence: 93%
“…It was not the purpose of this investigation to explore possible functions of cyclic AMP in photoreceptor transduction or adaptation, but Lipton et al (1977) did find some physiological evidence for a possible antagonism of the cyclic AMP and cyclic GMP systems in photoreceptors, and the possible role of cyclic GMP in transduction and/or adaptation is under active investigation (Yee and Liebman, 1978;Liebman and Pugh, 1979;Woodruff and Bownds, 1979;Biernbaum and Bownds, 1979;Kilbride, 1980;Kawamura and Bownds, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The plausibility of these suggestions rests on demonstrating appropriate correlations between the kinetics of the phosphodiesterase, cyclic GMP, and conductance changes measured in living receptor cells, and thus far definitive experiments have not been done. Kilbride and Ebrey (1979) and Kilbride (1980) have shown that illumination causes cyclic GMP levels of whole retinas to fall over a period of seconds, rather than milliseconds. Lowering calcium concentration in the Ringer's solution from 1.6 mM to a nanomolar level increases the cyclic GMP change.…”
Section: Introductionmentioning
confidence: 99%